Rewriting meat: Lab-grown meat in Türkiye - Ergin Zengin, Sezen (Meta, 2025)
With recent technological advances, lab-grown meat has been touted as a non-violent, environmentally friendly meat alternative. However, the success of lab-grown meat depends on how it is framed and perceived. This paper argues that lab-grown meat is a metaphorical translation, a rewriting, that aims to function in Turkish society. To investigate the manipulation of the patronage and the reception of lab-grown meat, a thematic analysis is conducted on a corpus of data representing public perception and the positions of various social actors that may influence the acceptance of lab-grown meat. The data includes public social media posts, news media articles, government announcements and interviews with scientists, as well as blog posts and videos from science YouTubers. The findings suggest that while political actors often engage in “translation as resistance,” effectively hindering the acceptance of lab-grown meat, the media and intellectuals play a pivotal role of “translation as mediation.” They work to recontextualize lab-grown meat positively, thereby crafting a more favorable public perception. This dynamic results in a spectrum of responses within Türkiye, ranging from opposition to acceptance. This paper argues that the metaphor of translation offers broader insights into the challenges of introducing novel foods, highlighting various cultural and political factors involved in the process. Translation can play an immense role in redefining the exploitative aspects of our food production and has the potential to reshape or perpetuate existing norms within the food industry.